2004
DOI: 10.1111/j.0001-5172.2004.0338.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal transcription of high‐affinity type‐2 cationic amino acid transporter is up‐regulated in LPS‐stimulated rodents

Abstract: We provide the first evidence to illustrate that sepsis/septic shock induces the transcription of high-affinity CAT-2B in renal tissues. Transcription of iNOS, CAT-2 and CAT-2B correlates well with renal NO biosynthesis. Regulation of L-Arg uptake by modulating the expression regulation of induced CAT-2 and CAT-2B might be a potential target for therapies against renal pathologic conditions related to NO overproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 37 publications
7
10
0
Order By: Relevance
“…Our data revealed that the expression of CAT‐2 A was not affected by LPS and/or platonin. These data are consistent with previous reports (23, 24), and further suggest that the role of CAT‐2 A in sepsis is negligible.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data revealed that the expression of CAT‐2 A was not affected by LPS and/or platonin. These data are consistent with previous reports (23, 24), and further suggest that the role of CAT‐2 A in sepsis is negligible.…”
Section: Discussionsupporting
confidence: 93%
“…Data from this study demonstrated that platonin may inhibit L‐arginine transport in LPS‐stimulated macrophages through inhibiting CAT‐2 and CAT‐2B expression. These data, together with our previous reports (22,23), support the idea that L‐arginine transport mediated by CAT‐2 and CAT‐2B is one crucial regulatory pathway that regulates iNOS activity. This study also investigated the effects of platonin on the low‐affinity CAT‐2 A expression in LPS‐stimulated murine macrophages.…”
Section: Discussionsupporting
confidence: 89%
“…These data, in concert with our previous ones [21][22][23], indicated that expression of CAT-2 and CAT-2B is organ-specific. In consistent with previous data [13], we also confirmed that CAT-2A, i.e., the low affinity alternative transcript of CAT-2, was constitutively expressed in rat lungs, kidney, and liver.…”
Section: Figsupporting
confidence: 89%
“…We employed LPS to induce sepsis, based on a previously described rodent model (6, 7). Briefly, sepsis was induced by intravenous (i.v.)…”
Section: Methodsmentioning
confidence: 99%
“…The protocols for NO measurement were adapted from our (6) as well as others' published articles (10, 11). The content of NO was quantified using a Sievers 280 NO analyzer (Sievers Inc., Boulder, CO).…”
Section: Methodsmentioning
confidence: 99%